Student Responses to the Implementation of MBKM (Study on FEB Students who follow International Course Asia University) - Astuti, Suryani Yuli; Rosiawan, Rizky Wahyudha; no, Suyit (CV. Inara, 2022)
The Ministry of Education and Culture enacted a new policy with the name Merdeka Learning Campus Merdeka (MBKM). The Independent Learning Program - Merdeka Campus is expected to be able to answer the challenges of higher education to produce graduates who are in accordance with the times, advances in science and technology, the demands of the business world and the industrial world, as well as the dynamics of society”. In response to this, the University of Muhammadiyah Lamongan held a student exchange program aimed at implementing the Independent Learning Campus (MBKM) policy. The student exchange program carried out by the University of Muhammadiyah Lamongan is the International Course at Asia University. On the other hand, The International Course activities require an evaluation to determine the level of effectiveness of the program and the benefits that students get as participants from these activities. The purpose of this study is to find out student responses to the MBKM program through: International Course Asia University implemented by Muhammadiyah University of Lamongan.